2023
DOI: 10.1002/smll.202302737
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Core–shell Sb2s3@Cds Nanorod with Enhanced Heterointerface Interaction for Chromium‐Containing Wastewater Treatment

Abstract: How to collaboratively reduce Cr(VI) and break Cr(III) complexes is a technical challenge to solve chromium‐containing wastewater (CCW) pollution. Solar photovoltaic (SPV) technology based on semiconductor materials is a potential strategy to solve this issue. Sb2S3 is a typical semiconductor material with total visible‐light harvesting capacity, but its large‐sized structure highly aggravates disordered photoexciton migration, accelerating the recombination kinetics and resulting low‐efficient photon utilizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Generally, Cr(VI) mainly exists in aqueous solution in two forms, namely, Cr 2 O 7 2− (acidic) and CrO 4 2− (basic), 39 in a chemical equilibrium with the concentration depending on the pH. Therefore, it is necessary to investigate the removal efficiency of Cr(VI) in a range of pH values.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Generally, Cr(VI) mainly exists in aqueous solution in two forms, namely, Cr 2 O 7 2− (acidic) and CrO 4 2− (basic), 39 in a chemical equilibrium with the concentration depending on the pH. Therefore, it is necessary to investigate the removal efficiency of Cr(VI) in a range of pH values.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…When the dosage of CdS was increased by 10 times, the BET surface area of Cu-CPs@CdS-3 synthesized by the same method was significantly reduced to 20 m 2 ·g –1 with a pore size of 18.98 nm (Figure S6). The result showed that nano-CdS could significantly increase the specific surface area of the heterojunction, exposing the most active sites in the photocatalytic reaction, which will be favorable for the adsorption of pollutants and the separation of photogenerated carriers …”
Section: Resultsmentioning
confidence: 99%
“…The result showed that nano-CdS could significantly increase the specific surface area of the heterojunction, exposing the most active sites in the photocatalytic reaction, which will be favorable for the adsorption of pollutants and the separation of photogenerated carriers. 41 4.2. Spectrum Analysis.…”
Section: Xrd Structural Analysismentioning
confidence: 99%
“…Photoabsorption capability is an important factor influencing the photocatalytic performance of photocatalysts, 50 and is usually evaluated by UV-vis diffuse reflectance spectra (DRS). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%